Hydrothermal Dynamics of Seasonally Frozen Soil With Different Vegetation Coverage in the Tianshan Mountains - Ma, Shen; Yang, Bin; Zhao, Jingyi; Tan, Changhai; Chen, Ji; Mei, Qihang; Hou, Xin (Frontiers in Earth Science, 2022)
The hydrothermal relationship between vegetation and seasonal frozen soil is one of the key research contents in the fields of permafrost ecological environment, hydrology and climate change in alpine mountainous areas. Based on the monitoring data of air temperature, precipitation and soil hydrothermal conditions at the depth of 0 to 5 m from site TS04 (with high vegetation coverage) and site TS05 (with low vegetation coverage) in the alpine grassland of the Tianshan Mountains, this study compared and analyzed the characteristics of freezing-thawing process, temperature and moisture changes of seasonal frozen soil with different vegetation coverage. The results show that the maximum seasonal freezing depth of the two sites is almost comparable, but site TS04 has a smaller freezing and thawing rate, and a shorter duration of freeze-thaw at all depths. TS04 also has a smaller annual range of surface temperature and ground-air temperature difference. The analysis indicates that vegetation acts as a thermal buffer and has a good thermal insulation effect on the ground surface. Site TS04 had high unfrozen water content in the unfrozen period and the water content increased with depth, while the unfrozen water content was low in site TS-05. In addition, the thresholds of soil water content response to rainfall events at 5 cm depth of site TS04 and site TS05 were 5 mm and 11 mm precipitation respectively, which indicated that the high vegetation coverage is conducive to rainwater infiltration, and the underlying soil of the site has a faster response to rainfall events.